EMBERDAYAAN PERAN KADER MELALUI POSYANDU REMAJA PLUS KIE KESEHATAN REPRODUKSI DI POSYANDU REMAJA KELURAHAN PENYENGAT RENDAH KOTA JAMBI - R Ruwayda (P3M Universitas Aisyiyah Surakarta, 2020)
The implementation integrated health center of adolences begins in 2018 at Aur Duri Primary Health Care, the number of adolescent visits has decreased due to one of them being established and there is no specific method in providing information and education communication (IEC) reproductive health. The target activities are 30 adolescents in Penyengat Rendah from April to June 2019. These community service activities through 3 stages of activity: the pre-implementation stage determining and obtaining a response letter from partners, arranging cooperation and determining goals activities, determine fun and flexible methods, determine activities which include lectures, discussion of Buzz Group methods and IEC practices. The implementation phase includes the provision of information about IEC through discussions using the Buzz Group and IEC practices. The post-implementation phase evaluates the knowledge and skills in providing IEC. The results of knowledge tests showed differences in the mean knowledge before and after using the Buzz Group of 3.133. The conclusion was level of achievement the target good, and adolescents feel the many benefits received increasing knowledge and skills of giving IEC to their peers. It is recommended for Primary Health care can develop this activity in other integrated health center of adolescent